Drought Reduces Release of Plant Matter Into Dissolved Organic Matter Potentially Restraining Ecosystem Recovery - Orme, Alice May; Lange, Markus; Schroeter, Simon Andreas; Wicke, Marcus; Kolle, Olaf; Pohnert, Georg; Gleixner, Gerd (Frontiers in Soil Science, 2022)
Future climate scenarios indicate increasing drought intensity that threatens ecosystem functioning. However, the behaviour of ecosystems during intense drought, such as the 2018 drought in Northern Europe, and their respective response following rewetting is not fully understood. We investigated the effect of drought on four different vegetation types in a temperate climate by analysing dissolved organic matter (DOM) concentration and composition present in soil leachate, and compared it to two accompanying years. DOM is known to play an important role in ecosystem recovery and holds information on matter flows between plants, soil microorganisms and soil organic matter. Knowledge about DOM opens the possibility to better disentangle the role of plants and microorganisms in ecosystem recovery. We found that the average annual DOM concentration significantly decreased during the 2018 drought year compared to the normal year. This suggests a stimulation of DOM release under normal conditions, which include a summer drought followed by a rewetting period. The rewetting period, which holds high DOM concentrations, was suppressed under more intense drought. Our detailed molecular analysis of DOM using ultrahigh resolution mass spectrometry showed that DOM present at the beginning of the rewetting period resembles plant matter, whereas in later phases the DOM molecular composition was modified by microorganisms. We observed this pattern in all four vegetation types analysed, although vegetation types differed in DOM concentration and composition. Our results suggest that plant matter drives ecosystem recovery and that increasing drought intensity may lower the potential for ecosystem recovery.